Peningkatan Hasil Belajar IPA dengan Strategi SQ3R (Survey, Question, Read, Recite, Review) Siswa Kelas 9.G SMP Negeri 2 Mataram - Martedi, Didik (Lembaga Yasin AlSys, 2022)
The purpose of this study was to find out: To find out science learning activities using the SQ3R (Survey, Question, Read, Recite, Review) method for class IX.G students of SMP Negeri 2 Mataram. To find out the increase in science learning outcomes using the SQ3R (Survey, Question, Read, Recite, Review) method for class IX.G students of SMP Negeri 2 Mataram. This research is a Classroom Action Research (CAR), using two cycles through the planning, action, observation, and reflection stages. As subjects in this study were class IX.G students for the 2021/2022 academic year with a total of 35 students, consisting of 16 male students and 19 female students. The results of this study indicate that: The SQ3R (Survey Question Read Recite Review) learning model strategy in science learning in the initial conditions was 68.57 with an average of 80.37 and in the first cycle the students' classical learning mastery was 82.86% with an average score average 83.91. In cycle II the classical student mastery was 100% with an average value of 91.29. Thus the SQ3R (Survey Question Read Recite Review) strategy in learning science can effectively improve student learning outcomes in class VII.I SMP Negeri 2 Mataram in science subjects. Student activity in learning with the SQ3R strategy (Survey Question Read Recite Review) in science learning in cycle I obtained a score of 65.00 with a score of 26 in the good category. In the activities of questions, reciting, presenting the results of group learning and concluding learning outcomes are included in the sufficient category, while the activity of answering questions through group discussions is still in the less category. The deficiencies that existed in cycle I were corrected in cycle II. Acquisition of student activity scores in cycle II increased to 33 in the very good category, with a value of 87.50. In cycle II students were able to carry out SQ3R (Survey Question Read Recite Review) activities in science learning well. Teacher activity in science learning with the SQ3R strategy (Survey Question Read Recite Review) in cycle I was 68.57% (fairly good category) and experienced an increase in cycle II of 85.71% (very good category).